The Role of ESG in Moderating Corporate Tax Avoidance and Firm Value - Kriswanti, Mantini; Indriani, Rini (Penerbit Goodwood, 2025)
Purpose: This study intends to examine how tax avoidance correlates with firm value, considering ESG factors as variables that influence the relationship. Methodology/approach: This study uses Ordinary Least Squares (OLS) Regression based on a sample of 47 companies traded on the IDX covering 2018 to 2023, by starting the analysis in 2017. The sampling method used is purposive sampling. To measure tax avoidance, this study uses CETR (Cash Effective Tax Rate), GETR (GAAP Effective Tax Rate), and BTD (Book-Tax Difference), while the evaluation of firm value is done through Tobin's Q. ESG rating is used to assess ESG performance. Results/findings: Tax avoidance with CETR has no significant effect on firm value, while GETR has a significant negative impact. In contrast, BTD shows a positive correlation. ESG as a moderator has no significant effect on CETR and BTD, but strengthens the negative impact of GETR on firm value. Conclusions: The impact of tax avoidance on firm value depends on the measurement method. ESG does not consistently weaken the relationship between tax avoidance and firm value. Limitations: The limitations of this study include research methods that do not fully address the statistical problems of autocorrelation and heteroscedasticity. Contribution: This study adds insight into the role of ESG in the relationship between tax avoidance and firm value. The results can serve as a guide for managers, investors, and regulators in evaluating tax strategies, sustainability, and firm valuation.